Effectiveness Of Tax Reduction Policies For Restaurants Using Tapping Boxes In Depok City - Carol Natasia Sarigodbless Br Simanjuntak; Prianto Budi Saptono (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the effectiveness of the 3% tax reduction policy for restaurant owners using the tapping box system in Depok City, which was initiated to enhance local revenue (PAD), improve taxpayer compliance in reporting, and strengthen regional competitiveness. The research applies Campbell's theory of effectiveness using a qualitative approach through literature review and in-depth interviews. Findings reveal that policy implementation faces several challenges, highlighting a gap between planning and field execution. Key obstacles include limited device availability, dependence on third parties, unequal access for MSMEs, technical difficulties, and insufficient outreach and equitable incentives. Program satisfaction also varies, with MSMEs facing more difficulties in accessing information and using the technology compared to larger businesses. Moreover, the policy’s heavy reliance on CSR funding from Bank BJB poses sustainability risks. Despite these issues, the policy has succeeded in boosting tax revenues by 20%, although its implementation remains uneven across business segments in Depok. The study recommends: (a) improving incentive design and cross-regional coordination to engage larger restaurants; (b) adopting inclusive policies, broader outreach, fair incentives, and strengthening bureaucratic capacity; (c) expanding technological access, intensive socialization, and transparent partnerships; (d) diversifying funding sources and providing technical support; and (e) promoting educational approaches, sustainable fiscal support, and digital and institutional innovation.